Universal Dependencies v2: An Evergrowing Multilingual Treebank Collection - Joakim Nivre; Marie-Catherine de Marneffe; Filip Ginter; Jan Hajič; Christopher D. Manning; Sampo Pyysalo; Sebastian Schuster; Francis Tyers; Daniel Zeman (France, 2022)
Universal Dependencies is an open community effort to create cross-linguistically consistent treebank annotation for many languages within a dependency-based lexicalist framework. The annotation consists in a linguistically motivated word segmentation; a morphological layer comprising lemmas, universal part-of-speech tags, and standardized morphological features; and a syntactic layer focusing on syntactic relations between predicates, arguments and modifiers. In this paper, we describe version 2 of the universal guidelines (UD v2), discuss the major changes from UD v1 to UD v2, and give an overview of the currently available treebanks for 90 languages.
Proceedings of the 12th Language Resources and Evaluation Conference